A Hyperchaotic Lorenz and DNA-Encoded Image Encryption Algorithm - Shuangyuan Li; Mengfan Li (Journal of Electrical and Computer Engineering)
In order to solve the problem that images are easy to leak and tamper during transmission and enhance the safety of image encryption, an image encryption algorithm based on deoxyribonucleic acid (DNA) coding and hyperchaotic Lorenz system is proposed. First, the hyperchaotic Lorenz system is proposed to replace the traditional logistic mapping algorithm so that the mapping range of the chaotic sequence reaches surjection, and the hyperchaotic Lorenz system is discretized using the fourth-order Runge–Kutta algorithm. The generated chaotic sequence is encoded according to DNA coding rules, and the encoded image is encrypted and scrambled by using the index of chaotic sequence. Finally, DNA algorithm rules are used for diffusion processing to obtain the ciphertext image. Key space analysis, histogram analysis, correlation analysis of adjacent pixels, and information entropy analysis of the algorithm results are performed. Meanwhile, the mean square error (MSE) of pepper and salt noise density is analyzed by the peak signal-to-noise ratio (PSNR). It shows that the algorithm can resist various external attacks and has high security.